Candidate gene mutations of patients with astrocytoma who present with seizures: evidence from whole exome sequencing - Phabphal, Kanitpong; Choochuen, Pongsakorn; Kaewborisutsakul, Anukoon; Tunthanathip, Thara; Sangkhathat, Surasak (Frontiers in Oncology, 2025)
Epileptic seizures are common and substantially impact long-term quality of life. However, the risk factors for preoperative seizures among patients with astrocytomas remain unclear. This study aimed to identify the candidate genes associated with seizure before operation among patients with astrocytomas. We conducted a single-center cohort study including 34 patients with astrocytomas that presented with or without preoperative seizures and analyzed differential gene expression, evaluating a total of 142 candidate genes, selected based on a literature review, and categorized into functional groups (e.g., glutamatergic, oncogenic, chromatin-modifying). Clinical characteristics, including age, sex, tumor location, grade, and size, and peritumoral edema, were similar between the seizure and non-seizure groups. Glutamate receptor mutations were identified in 15% of the non-seizure group and 78.6% of the seizure group. Patients with astrocytomas who presented with seizures had significantly more mutations in glutamate-related genes, including NMDA (64.3% vs. 20%, p = 0.01) and IDH1 (42.7% vs. 10%, p = 0.04). Group III metabotropic glutamate receptor alterations were found in 1 patient in the non-seizure group (n = 19) and in 5 patients in the seizure group (n = 9) (p = 0.06). No significant differences were observed in other glutamate receptors subtypes or related genes. In conclusion, seizures in patients with astrocytomas are associated with IDH1 and NMDA receptor mutations, rather than other clinicopathological factors or other glutamate-related genes. Future research should involve larger multicenter studies and conduct a functional analysis to identify new treatment targets and provide additional evidence to guide clinical decision-making.